2001
DOI: 10.1007/s003830000485
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic removal of tracheobroncheal foreign bodies: value of patient history and timing

Abstract: Between 1990 and 1999, 741 bronchoscopic procedures were performed in 698 children, 594 of whom were evaluated for foreign-body aspiration (FBA) (mean age 3.9 years, male:female 287/307). Based on the presenting symptoms, clinical outcome, and complications, two major groups were identified. Group 1 consisted of 438 patients with a definitive history of FBA. Most were admitted soon after the aspiration with sudden onset of symptoms such as coughing, choking, wheezing, and respiratory distress. Group 2 comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
2
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 0 publications
4
36
2
7
Order By: Relevance
“…(20) Likewise, the predominance of male patients can be explained by the fact that boys are typically more curious and adventurous. (7) The principal signs and symptoms observed (dyspnea, cough and diffuse crackles) are in accordance with findings in the literature (1,3,18) and can be explained by the long time elapsed between the FBA episode and the endoscopy, such a delay typically being described as responsible for the increase of morbidity and as a risk factor for treatment failure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(20) Likewise, the predominance of male patients can be explained by the fact that boys are typically more curious and adventurous. (7) The principal signs and symptoms observed (dyspnea, cough and diffuse crackles) are in accordance with findings in the literature (1,3,18) and can be explained by the long time elapsed between the FBA episode and the endoscopy, such a delay typically being described as responsible for the increase of morbidity and as a risk factor for treatment failure.…”
Section: Discussionsupporting
confidence: 88%
“…(1,2) Occurring principally in the three first months of life, FBA is influenced by socioeconomic, cultural and educational factors, which determine the frequency and particularities of the foreign body aspirated. (3)(4)(5)(6) The most common complications include inflammation, laryngospasm, chronic bronchitis and pneumonia. (7) Serious complications, such as severe airway obstruction and death, tend to occur in young children due to the small caliber of their airways.…”
Section: Introductionmentioning
confidence: 99%
“…Emir et al [10], concluded in their study that cases with chronic pulmonary infection and late presentation are at higher risk of developing complications and care should be taken in deciding the timing of bronchoscopy in this group to avoid life threatening complications. The ventilating rigid bronchoscopy under general anaesthesia remains the gold standard for the safe removal of tracheobronchial foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…Aspiration of foreign body has a significant morbidity rate and can cause mortality in about 7% of cases [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Although there have been significant advances in pediatric endoscopic airway management, the occurrence of FBA has not changed significantly [3].The increased risk of aspiration in children during the first three years of life is attributed to many factors including: inadequately developed posterior dentition, immature neuromuscular mechanisms of both deglutition and airway protection, and the ubiquitous tendency of children below 3 years of age to put objects into their mouths [22].…”
Section: Introductionmentioning
confidence: 99%